Durabilidad de madera termotratada de Gmelina arborea (Roxb. ex Sm) y Tectona grandis (L.f.) en Costa Rica - Fallas-Valverde, Lucía Isabel (Instituto Tecnológico de Costa Rica, 2015)
Wood is a biological material composed of cellulose, hemicellulose and lignin. It has been used through the years in outdoors and indoors. However, it is susceptible to degradation, for that reason some techniques have been developed to improve their resistance to biodegradation, such as thermal- treatment. This research assessed the durability of heat-treated wood of Tectona grandis and Gmelina arborea under five different temperatures of heat treatment, the evaluation was done by accelerated laboratory tests and exposure to soil test. Wood heat treated under five different temperatures of heat treatment was evaluated by an accelerated laboratory test of natural decay, using two wood decay fungi (Lenzites acuta and Trametes versicolor) for 16 weeks and by a field test with stakes under an exposure time of 300 days, the main objetive of this was to study the properties of mechanical resistance of thermally treated wood, analyzing the modulus of elasticity, modulus of rupture and dynamic modulus of elasticity, in two different environmental conditions. We concluded that the heat-treated wood had a higher resistance with increasing treatment temperature; this improved the strength properties of wood in the forest species studied. Finally it was concluded that the temperature of heat-treated at 200 °C, allowed the best results in terms of mechanical properties of wood and in resistence against abiotic degradation for both species.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2015.
Keywords: Biodeterioro; Termo-tratamiento; Trametes versicolor; Madera lenzites; Agentes abióticos